An effort to Improve the Quality of Workers at the Makassar city Department of Employment Services - Daraba, Dahyar; Subianto, Alim Bachri; Salam, Rudi (Jurnal Ilmiah Ilmu Administrasi Publik, 2018)
The quality of labor is a major factor in the supply of human resources. This study aims to find out the efforts made to improve the quality of the workforce at the Manpower Office in Makassar City. The research approach used uses qualitative research. Research informants are people who obtain employment services at the Manpower Office. Data collection is done through interviews, observations and data collection in the field. The data analysis technique uses interactive models such as: data reduction, data condensation, data presentation and conclusion drawing. The results of this study indicate that there are still various shortcomings such as the analysis of the needs of employees with special expertise and training systems that still do not meet expectations. Furthermore, inventory of office facilities and infrastructure that are less well maintained.